Perfil de sensibilidade antimicrobiana e detecção de genes de resistência em cepas de klebsiella pneumoniae isoladas de pacientes assistidos em um hospital terciário da região norte do Ceará - Silva, Martinair Santana da (2024)
Antibiotic resistance represents a substantial concern in healthcare systems around the world. The main mechanism that drives the rapid spread of multidrug-resistant strains in hospital environments is the acquisition of resistance genes. The aim of this study was to analyze the antimicrobial sensitivity profile and identify the presence of resistance genes in Klebsiella pneumoniae isolated from patients treated at a tertiary hospital in the state of Ceará, Brazil. From April/2021 to May/2022, 56 specimens of this carbapenem-resistant microorganism were collected. Bacterial identification and sensitivity profile were performed on the automated VITEK®2 system (bioMérieux), molecular analysis of the bla KPC, NDM, OXA-48 and IMP genes was performed by conventional polymerase chain reaction. Among the patients from whom these microorganisms were isolated, the gender ratio was proportional to 50%, the bacteria were isolated mainly from blood (42.8%), with 44.6% of cases related to Healthcare-Associated Infections (HAIs). Regarding sensitivity to antimicrobials, all were resistant to cephal osporins, ceftazidime and cefepime. On the other hand, the majority (96.4%) were sensitive to Colistin. Of the strains analyzed, 92.8% were multidrug resistant (MDR), while 3.5% were extensively resistant (XDR). The bla NDM gene was the most prevalent, detected in 51.8% of isolates, followed by bla KPC(17.8%), blaIMP (7.2%) and blaOXA-48 (5.3%). Furthermore, 8.9% of the isolates showed coexistence with bla NDM/KPC and 1.8% with bla KPC/OXA-48. In this study, all strains tested were resistant to some antibiotics from the carbapenem class, mainly to Ertapenem. Among the other antibiotics tested, the most effective was Colistin. Most of the strains were collected from patients' blood and the hospitalization sector with the highest number of collections was the surgical center.Another alarming fact is that more than half of hospitalized patients were admitted due to community-acquired infections. A high prevalence of resistance genes studied was also observed,with emphasis on bla NDMand bla KPC, with a significant relationship being found between the presence of the bla NDM gene and the resistance of the microorganism to the antibiotic Imipenem